Inhibition of Protein Degradation Induces Apoptosis through a Microtubule-Associated Protein 1 Light Chain 3-Mediated Activation of Caspase-8 at Intracellular Membranes - Pan, Ji-An (American Society for Microbiology, 2011)

(untitled)
The accumulation of damaged or misfolded proteins, if unresolved, can lead to a detrimental consequence within cells termed proteotoxicity. Since cancerous cells often display elevated protein synthesis and by-product disposal, inhibition of the protein degradation pathways is an emerging approach for cancer therapy. However, the molecular mechanism underlying proteotoxicity remains largely unclear. We show here that inhibition of proteasomal degradation results in an increased oligomerization and activation of caspase-8 on the cytosolic side of intracellular membranes. This enhanced caspase-8 oligomerization and activation are promoted through its interaction with the ubiquitin-binding protein SQSTM1/p62 and the microtubule-associated protein light chain 3 (LC3), which are enriched at intracellular membranes in response to proteotoxic stress. Silencing LC3 by shRNA, or the LC3 mutants defective in membrane localization or p62 interaction fail to induce caspase-8 activation and apoptosis. Our results unveiled a previously unknown mechanism through which disruption of protein homeostasis induces caspase-8 oligomerization, activation, and apoptosis.